New Insights into Anxiety Disorders - Durbano, Federico (IntechOpen, 2013)
This book collects the contributions of a number of clinical psychiatrists all over the world, interested in developing basic research about anxiety and in applying it in clinical contexts. It is divided into four sections, covering general issues about anxiety (ethological and developmental ones), basic research issues on specific aspects of anxiety (bioanatomical ones, correlation with personality structure and so on), and new clinical and therapeutical proposals and hypothesis. Each author summarized the clinical importance of his work, underlining the clinical pitfalls of this publication.